CONSUMER’S CHARACTERISTICS AND ATTITUDES TOWARDS ORGANIC FOOD PRODUCTS IN TIMES OF COVID-19 PANDEMIC - Vapa Tankosić, Jelena; Hanić, Hasan; Bugarčić , Milica (Economics of Agriculture, 2022)
The pandemic caused by the Covid-19 virus significantly affected the consumers’ behavior. The subject of the paper is to analyze the consumer characteristics, the consumer attitudes towards organic food products, as well as the changes in the consumer behavior. The research was performed in 2021 in the Republic of Serbia. The statistical software package SPSS has been utilized for data analysis. Our findings show that, in times of COVID-19 pandemic, the consumers have a very positive perception of nutritional values of organic food products with an expressed willingness to pay 20–30% more for the organic products, in regard to conventional products. The main reason for buying such products is less chemistry and child health. The main reason for insufficient consumption is the high price. The monthly income of irregular consumers of organic food products has predicted the willingness to pay, while the household size has predicted the assessment of the organic products nutritional properties.